Effect of oat bran and barley grain addition on physico-chemical and organoleptic properties of Shrikhand - Uma, Karpurapu; Balasubramanyam, BV; Emerald, F Magdaline Eljeeva; Vimala, R (Indian Journal of Dairy Science, 2018)
Shrikhand is a sweetish-sour, fermented milk product and it has a typical semi-solid consistency with a characteristic smoothness and firmness. It is rich in fat, protein and carbohydrates, but lacks in dietary fibre particularly Î²-glucan, is an important component of a balanced diet because of its functional attributes. This present investigation was carried out to standardize the technology for production of shrikhand with oat bran and barley as a source of Î²-glucan. The incorporation of oat bran up to 4%, barley up to 3% and mixture (1:1) of oat bran & barley up to 4% in shrikhand was found to produce the product which was comparable to control sample. The Î²-glucan in shrikhand samples containing barley, oat bran and their mixture was 0.247, 0.310 and 0.317% respectively. The rheological studies showed that the addition of oat bran and barley increased the firmness and consistency of the shrikhand samples.Â